SOSIALISASI DAN PENGABDIAN KEPADA MASYARAKAT BERDASARKAN NILAI BERBUDILUHUR DI TENGAH PANDEMI COVID-19 - Umaimah Wahid; Wendi Usino; Nawiroh Vera; M. Alfansyah Harahap; Geri Suratno; Imelda Imelda; Anastasya Putri Christanty; Mulyati Mulyati (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The COVID-19 pandemi has changed the world in all sectors, particularly the health, economy, and education sectors. World Health Organization (WHO) announced the coronavirus outbreak (COVID-19) as a global pandemi. Therefore each country began implementing social distancing policies. The President of Indonesia insists on doing all activities from home: work at home, study at home and worship at home. Budi Luhur University carried out the President's appeal by carrying out work and learning activities from home by prioritizing the health and safety of the entire academic community. It is also a form of value embodiment of responsibility, cooperation, love, mutual help, being patient, and being grateful for the situation during a pandemi. Services are provided in the form of personal protective equipment (PPE) to hospitals around Jakarta to protect doctors and health workers. The services implemented also consist of socializing to the public about social distancing, washing hands regularly, wearing masks, staying at home campaigns, and providing handwashing places for online taxi bike drivers. The strategic steps exerted in the form of dedication to various communities are based on human values and the embodiment of the mental attitude of the philosophical value